Response to Tyrosine Kinase Inhibitors in Myeloproliferative Neoplasia with 8p11 Translocation and CEP110‐FGFR1 Rearrangement. (27th February 2017) - Wehrli, Marc; Oppliger Leibundgut, Elisabeth; Gattiker, Heinrich H.; Manz, Markus G.; Müller, Antonia M.S.; Goede, Jeroen S.
Abstract : This brief communication reports on a patient with an exceedingly rare "8p11 (eight‐p‐eleven) myeloproliferative syndrome" (EMS) with CEP110‐FGFR1 rearrangement who responded to treatment with the multi‐tyrosine kinase inhibitor (TKI) dasatinib. Dasatinib improved quality of life substantially by increasing blood counts and reducing the need for transfusions. This report demonstrates that the second‐generation TKI may provide a therapeutic option for elderly and frail EMS patients who cannot be offered aggressive therapy, including allogeneic hematopoietic cell transplantation. Abstract : The case of a patient with the rare "8p11 (eight‐p‐eleven) myeloproliferative syndrome" with CEP‐FGFR1 rearrangement is reported.